8-3(x+2)=11

Simple and best practice solution for 8-3(x+2)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-3(x+2)=11 equation:


Simplifying
8 + -3(x + 2) = 11

Reorder the terms:
8 + -3(2 + x) = 11
8 + (2 * -3 + x * -3) = 11
8 + (-6 + -3x) = 11

Combine like terms: 8 + -6 = 2
2 + -3x = 11

Solving
2 + -3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -3x = 11 + -2

Combine like terms: 2 + -2 = 0
0 + -3x = 11 + -2
-3x = 11 + -2

Combine like terms: 11 + -2 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| 2+4b=10 | | 9x+8=4x+36 | | 30x-3=x+12 | | -6x+10=40 | | 2*(a+bc)+cb+ab+ac-3*(ab-cb-ba+bc)= | | 35b-8=4 | | -2x+16=-8 | | 9x^2-27x+14= | | 4x^2-33x+8= | | 33=-3(4+5t) | | 33=-3(4+5t) | | 6n-4=38 | | 10m+3n-6m+8n= | | 8x^2+14x+3= | | 3n+3=2n+8 | | 8y-5=5y+4 | | 3(3c-1)-3=4c+9 | | 7x^2-16x+9=0 | | 8x^2+14+3= | | 5n-16=n+20 | | 4t-7=5(t+6) | | (7-a)(4-3a)=x | | 3x^2+17x+20= | | 10n+17=3n+52 | | 25+2y-9=9y-12-3y | | 9n+14=6n+29 | | 5x^2+17x+6= | | 8n-3=2n+39 | | 6x-18=-8 | | tg(2x)=1 | | 3(4-2s)=30 | | 5n-10=3n+50 |

Equations solver categories